THE INFLUENCE OF USING GUESSING MEANING THROUGH CONTEXT STRATEGY OF STUDENTS’ READING ABILITY TO TEACH NARRATIVE TEXT TO TENTH GRADERS OF SMAN 1 PARE (RETAIN, 2016)
THE INFLUENCE OF USING GUESSING MEANING THROUGH CONTEXT STRATEGY OF STUDENTS’ READING ABILITY TO TEACH NARRATIVE TEXT TO TENTH GRADERS OF SMAN 1 PARE Rifqi Zunaida English Education Department, Language and Arts Faculty, Surabaya State University Email: rifqizunaida@mhs.unesa.ac.id Fauris Zuhri, S.Pd., M.Pd. English Education Department, Language and Arts Faculty, Surabaya State University Email: fauriszuhri@unesa.ac.id Abstract Reading is one of English skills which should be mastered by the students. Through reading, the students get various kinds of knowledge as well as they comprehend the context of the text. Since reading deals with comprehension of the text, the appropriate reading strategy is need by the students. Students of senior high school find many difficulties in understanding a text that they have already read because they find many unfamiliar words, ambiguous phrases or sentences in the text. They frequently make incorrect guessing about meaning even when the students have been trained to use all semantic and syntactic clues available (Prince, 1996:480). Those are because most of students do not know the strategies for reading comprehension (Brown, 2001). Brown (2001) also states that the appropriate strategy to comprehend reading text is using guessing meaning context strategy. So that, the researcher conducts this study in order to know if there is a significant difference of students’ reading ability after being taught by using strategy of guessing meaning through context. This study uses quantitative pre-experimental research design. Moreover, one group pretest-posttest was used in this research. The subject is the tenth graders of SMAN 1 Pare. The students’ pretest and posttest scores are then compared using independent sample T-test in SPSS 16. The result shows that there is a significant difference of students’ reading abilities after being taught by using the strategy of guessing meaning through context. It was proven by the means of post-test scores which are higher than those of the pre-test whose different score reaches 83,25. Moreover, the sig (2-tailed) is 0.02 which is lower than 0.05. In addition, this strategy has the large effect to the students’ reading ability which shows 0.53 (eta squared calculation), it means that this strategy is appropriate to be applied in reading class. Keywords: Reading ability, Teaching reading, Narrative text, Strategy of guessing meaning through context Abstrak Membaca adalah salah satu skil dalam bahasa Inggris yang harus dikuasai oleh siswa. Melalui membaca, seorang siswa menperoleh berbagai macam ilmu pengetahuan sebaik mereka memahami suatu teks bacaan. Sejak reading berhubungan dengan pemahaman teks, strategy membaca yang cocok untuk siswa sangantlah diperlukan. Siswa sekolah menengah atas kebanyakan menemukan kesulitan dalam memahami suatu bacaan teks yang telah mereka baca karena mereka menemukan kata yang tidak familiar, prase dan kalimat yang ambigu di dalam suatu bacaan. Siswa sering kali melakukan kesalahan penebakan arti kata dalam suatu bacaan meskipun telah diajarkan penggunaan sintak dan semantik clue dalam suatu kalimat (Prince, 1996:480). Itu semua disebabkan karena kebanyakan siswa tidak mengetahui strategy yang baik untuk memahami suatu bacaan (Brown, 2001). Brown juga berpendapat bahwa penerapan strategy yang cocok untuk memahami suatu bacaan adalah menggunakan strategy penebakan arti kata sesuai konteks. Maka dari itu, peneliti melakukan penelitian in dengan tujuan untuk mengetahui bahwa adakah pengaruh perbedaan kemampuan siswa setelah strategi penebakan arti kata sesuai konteks tersebut diimplementasikan. Penelitian ini menggunakan desain penelitian quantitaive pre-experimental . Selain itu, satu group pre-test dan post-test juga digunakan dalam penelitian ini. Subyek penelitian ini adalah kelas X SMAN 1 PARE. Kemudian, nilai dari pre-test dan post-test siswa dibandingkan menggunakan Independent Smaple T-Test dalam SPSS 16. Hasil dari perhitungan tersebut menunjukkan bahwa ada perbedaan signifikan dari kemampuan membaca siswa setelah strategy penebakan arti sesuai konteks diterapkan. Itu dibuktikan melalui mean dari nilai post-test yang lebih tinggi dari nilai pre-test yang telah mencapai 83,25. Selain itu, nilai sig (2-tailed) adalah 0.02 yang lebih rendah dari 0.05. Apalagi, strategi ini juga mempunyai effect yang cukup besar yang menunjukkan angka 0.53 (menggunakan rumus Eta Squared) terhadap kemampuan membaca siswa. Jadi, itu menunjukkan bahwa strategi tersebut memang cocok diterapkan dalam kelas reading. Kata Kunci: Kemampuan membaca, Pengajaran membaca, teks narrativet, Strategy Penebakan Arti Kata Sesuai Konteks.